Managing Agricultural Risk at the Country Level : The Case of Index-Based Livestock Insurance in Mongolia - Mahul, Olivier; Skees, Jerry (World Bank, Washington, DC, 2012)
This paper describes the index-based livestock insurance program in Mongolia designed in the context of a World Bank lending operation with Government of Mongolia and implemented on a pilot basis in 2005. This program involves a combination of self-insurance by herders, market-based insurance, and social insurance. Herders retain small losses, larger losses are transferred to the private insurance industry, and extreme or catastrophic losses are transferred to the government using a public safety net program. A syndicate pooling arrangement protects participating insurance companies against excessive insured losses, with excess of loss reinsurance provided by the government. The fiscal exposure of Government of Mongolia toward the most extreme losses is protected with a contingent credit facility. The insurance program relies on a mortality rate index by species in each local region. The index provides strong incentives to individual herders to continue to manage their herds so as to minimize the impacts of major livestock mortality events; individual herders receive an insurance payout based on the local mortality, irrespective of their individual losses. This project offered the first opportunity to design and implement an agriculture insurance program using a country-wide agricultural risk management approach. During the first sales season, 7 percent of the herders in the three pilot regions purchased the insurance product.